Symposium on “Climate Change and Molluscan Ecophysiology” at the 79th Annual Meeting of the American Malacological Society - Marko, Peter B. (2020)
Climate change has already had many observable effects on Earth. On land, glaciers and snowpacks have shrunk, tropical forests are being replaced by savannahs, and coastal areas have increased risks of flooding (e.g., IPCC 2007, Allan and Soden 2008, Dai 2010, NOAA 2010, Chen et al. 2011). In addition to sea-surface warming, climate change has altered the physical and chemical nature of the marine environment, including ocean acidification and expanding hypoxia. The scope and scale of future environmental change that individuals will undergo on land and in the sea will fundamentally influence the ecological and evolutionary responses of populations and species, dependent on their evolved physiological capacities for environmental tolerance (Parmesan 2006, Hoffmann and Sgrò 2011, Kuntner et al. 2014). Although climate change will affect all organisms, molluscs are unique in many respects, and, given their high diversity and evolutionarily flexible body plan, they provide several established and emerging models systems for comparative physiological study in nearly all types of ecosystems, from rivers to rocky shores and deserts to the deep sea. Moreover, many mollusks play pivotal roles as consumers, predators, and competitors in a diversity of ecosystems and habitats. Mollusks also have great economic importance, with many species of mollusks harvested by humans for food, either from natural populations or from aquaculture. The joint meeting of the American Malacological Society and the World Congress of Malacology in Ponta Delgada, Azores, on July 23rd 2013, brought together malacologists actively pursuing research aimed at addressing the direct and indirect impacts of climate change and the mechanisms mollusks use to compensate for these changes, their natural evolved tolerances, and the energetic, ecological, and biogeographic consequences of compensation. The goal for this symposium was to expose a broad range of malacologists to ecophysiological approaches in the hopes of recruiting and stimulating interest in the emerging questions of this field. Speakers included those whose talks addressed the effects of climate change on mollusks across a wide range of time scales and levels of biological organization, describing the results from recent research as well as considerations of some of the challenges facing ecophysiological research on mollusks in the future.